Evaluating the Lifelong Learning Approach to Demand-Oriented Research in Student Theses Using the ADDIE Model - Abolghasem Rahmani; Pooria Gill; Siavash Moradi; Atefeh Zabihi Zazoly; Fattane Amuei; adele Rafati (Journal of Mazandaran University of Medical Sciences)
Background and purpose: The significance of educational theses and their contribution to addressing societal needs is widely recognized. A considerable amount of research is conducted through student theses, which serve both educational and research objectives. The thesis, in this context, encompasses a hidden curriculum that requires the teaching of research skills and the management of educational opportunities to achieve these goals. In this regard, the Department of Medical Nanotechnology at Mazandaran University of Medical Sciences implemented an educational program aimed at fostering demand-oriented research in the form of a master's thesis. This study utilized components of the lifelong learning approach and the steps of the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model for educational design. By integrating these frameworks, the program aimed to enhance both demand-oriented research and the development of lifelong learning competencies in students. The purpose of this study was to assess the effectiveness of this program from the perspective of master's students in nanotechnology. Materials and methods: This study employed a conventional qualitative method of content analysis, combined with an action research approach, to gather data. The primary data collection tool was individual semi-structured interviews conducted with master's students. Results: An analysis of the participants' comments revealed that the majority expressed satisfaction with the implementation of the program, using terms such as "suitability of the strategy", "attention to societal needs", "creation of job opportunities" and "focus on students". Based on the data, the learners' responses were categorized into four main themes and nine subthemes. Conclusion: From the students' perspective, this program has proven to be both useful and practical in preparing them for their future careers. They highlighted its key benefits, including enhancing critical thinking, motivating and fostering creativity, and facilitating communication with various institutions within the target market.